Mineralogy of Gypsiferous Soil and the Effect of a dditiveLime Stone waste powder on its Physical Properties - Rashid, Thalar Othman; Majeed, Nadhmia Najmaddin (Iraqi Journal of Science, 2020)
The presence of gypsum in soil as bonding agent alters its behavior with a large influence on itsphysical properties.Soil samples were taken from two locations of different gypsum content(S1 = 30.5% and S2= 20%) inMakhmur area. TheUnified soil classification system indicated that soil type was clay with low plasticity(CL). Basic methods of physical testing of soils, such as grain size analysis,specific gravity and atterberg limit were applied. Stabilizationof the gypsiferous soil was performed by addinglimestone waste powder takenfrom Said sadiqandPirmam areas,with different percentages(5%, 15%,25%).The results show that the addition of limestone powder to the tested soils decreases their liquid and plastic limits.